Implementasi Assertive Training untuk Meningkatkan Komunikasi Interkultural dan Mencegah Konflik Pemuda Lintas Etnis - Felix Trisuko Nugroho; Bernardus Widodo (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Indonesia's cultural diversity presents opportunities for social cohesion while also increasing the risk of intercultural conflict among youth. This study examined the effectiveness of Assertive Training within a multicultural counseling framework in improving intercultural communication and preventing conflict among cross-ethnic youth. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. The participants were university students from diverse ethnic backgrounds studying in a multicultural campus environment. Data were collected using the Assertiveness Assessment Scale, both of which met validity and reliability requirements. Data were analyzed using descriptive statistics, paired sample t-tests, and independent sample t-tests. The findings revealed that participants who received Assertive Training demonstrated substantially greater improvement in intercultural communication and conflict prevention than those in the control group. The intervention also strengthened participants' ability to express opinions assertively, respect cultural differences, and resolve interpersonal disagreements constructively. These findings indicate that Assertive Training is an effective behavioral intervention for enhancing intercultural competence and can be integrated into multicultural counseling programs to promote social harmony and prevent conflict in culturally diverse communities.